Feeling your data: Touch and making sense of personal digital data. (October 2017) - Lupton, Deborah
People's encounters and entanglements with the personal digital data that they generate is a new and compelling area of research interest in this age of the ascendancy of digital data. Masses of personal information are constantly generated via people's use of digital technologies and used for a variety of purposes by a range of actors. People are faced with the conundrum of how to interpret, control and make sense of their lively data. In this article, I explore the topic of how personal digital data and their circulations can be made more perceptible and therefore interpretable to people with the use of three-dimensional materialisations. These materialisations invite users to 'feel your data'. As I show, 'feeling your data' has two meanings: the sensations of touching these three-dimensional objects and the visceral responses that are generated from these and other sensory encounters with data.